The utility of the integrated behavior change model as an extension of the theory of planned behavior - More, Kimberly R.; Phillips, L. Alison (Frontiers in Psychology, 2022)
Introduction: There are several widely used theories of health behaviour change, which mostly utilize the social cognitive approach. These theories tend to posit that intention is a direct predictor of behaviour, do not include automatic influences on behaviour, and propose a one-size-fits-all theory for both initiators and maintainers. However, the intention-behaviour gap is a well-observed phenomenon, researchers have highlighted that both automatic and deliberative factors promote behavioural engagement, and predictors of behaviour have been shown to differ between initiators and maintainers—three issues that necessitate theory advancement. To that end, the present research compares the utility of the Integrated Behaviour Change Model (IBCM) – a social cognitive model that includes automatic factors involved in behavioural engagement and a moderator of the intention-behaviour gap – to its theoretical predecessor, the Theory of Planned Behaviour (TPB). Further, the relevance of the IBCM factors for predicting exercise behaviour is compared in initiators versus maintainers. Method: Participants were 494 US undergraduates. Participants reported on variables from the IBCM (and TPB) at baseline and reported on their exercise behaviour in two surveys at seven- and 14-days post-baseline. Results: Findings supported the first hypothesis that the IBCM would be more relevant for initiators in comparison with maintainers, using structural equation modelling. Specifically, only the paths between intrinsic motivation and affective attitude, affective attitude and intention, and intention and behaviour were reliably found for maintainers. For initiators, the aforementioned paths were also reliably support and the additional following paths were also supported: intrinsic motivation and perceived behavioural control, perceived behavioural control and intention, and intention and action planning. However, results did not support the second hypothesis that the IBCM would predict significantly more variance in behaviour than its theoretical predecessor, the TPB. Specifically, the addition of action planning, implicit attitude, and implicit motivation only predicted an additional 1.5% (p > .05) of the variance in exercise behaviour above and beyond intention. Conclusion: Results highlight the continued need for theoretical refinement in terms of delineating mechanisms of initiation and maintenance and the need for further development in terms of improving upon current predictions of behaviour engagement and change.